ANALISIS PENERIMAAN DAN FAKTOR-FAKTOR YANG MEMENGARUHI PRODUKSI BUDIDAYA ANGGREK DENDROBIUM DI KABUPATEN SLEMAN - Anggraeni, Rini; Mufidah, Husnul; Kadarso, Kadarso (Agros Journal of Agriculture Science, 2024)
Orchid plants have distinctive aesthetic characteristics as room decoration, because of their beauty and fragrant aroma. From an economic perspective, orchid plants play a role in building the community's economy because they can open up opportunities and provide income for households in Sleman Regency. The research objectives were to determine (1) the acceptance of the Dendrobium Orchid farming business; (2) factors that influence the production of Dendrobium Orchid farming in Sleman Regency. The method used in this research is a quantitative descriptive analysis method. The research location was determined purposively. Respondents were determined using the snowball sampling method with 30 respondents. Data were analyzed using (1) acceptance analysis and (2) multiple linear regression analysis. The results of the research show that (1) income from farming is IDR 49,260,594/farming/year or greater than the total production costs, namely IDR 22,204,237/farming/year; (2) land area (X1) and fertilizer (X3) are factors that influence the production of Dendrobium Orchid farming in Sleman Regency.